Vibrio parahaemolyticus and Vibrio cholerae contamination of green mussels (Perna viridis) harvested from Cavite and Pangasinan, Philippines - Lagazon, Patricia Mae Mallari (College of Home Economics, University of the Philippines Diliman, 2023)
Contamination with Vibrio parahaemolyticus and Vibrio cholerae of green mussel and its growing waters in Cavite and Pangasinan, Philippines was established.. Survey of food safety practices (based on the provisions of PNS/BAFS 207:2017 and Codex Alimentarius (CXC 52-2003) of green mussel farmers from Cavite and Pangasinan using targeted sampling was conducted. Microbiological quality of green mussels and seawater as well as the physico-chemical parameters of the seawater were determined followed by detection and identification of Vibrio parahaemolyticus and Vibrio cholera using Polymerase Chain Reaction. Most respondents were non-compliant, and socio-economic and demographic explanatory variable is associated with the compliance of green mussel farmers to GAqP. All samples (i.e., green mussels and seawater) from Pangasinan were compliant to various Philippine standards. Meanwhile municipalities in Cavite reported microbiological and physico-chemical results above reference standards. Further, linear regression models imply that the microbiological quality of green mussel were highly influenced by the microbiological and physico-chemical characteristics of the seawater were they are harvested. Vibrio parahaemolyticus in green mussel samples and in seawater samples were detected using tlh primers. Presence of V. cholerae are detected in green mussel and seawater samples using ctxA, tcpA, and ompW PCR primers. These findings indicate that there is a potential food safety risk from microbiological hazards including V. parahaemolyticus and V. cholerae that may be present in the consumption of green mussel is likely.